A generalized case of purpura annularis telangiectoides of Majocchi - Seray Külcü Çakmak; Duru Onan; Emine Tamer; Nuran All?; Ferda Artüz; Servet Güreşçi (Our Dermatology Online, 2015)
Purpura annularis telangiectoides is a rare form of pigmented purpuric dermatoses which usually presents as annular patches with central clearing on the lower extremities. We present an atypical presentation of purpura annularis telangiectoides with generalized lesions in an elderly woman